2017
DOI: 10.1186/s12052-017-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effectiveness of two natural selection simulations in the context of a large-enrollment undergraduate laboratory class

Abstract: Background: Simulations can be an active and engaging way for students to learn about natural selection, and many have been developed, including both physical and virtual simulations. In this study we assessed the student experience of, and learning from, two natural selection simulations, one physical and one virtual, in a large enrollment introductory biology lab course. We assigned students to treatments (the physical or virtual simulation activity) by section and assessed their understanding of natural sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
9
0
3
Order By: Relevance
“…Moreover, various studies have shown that virtual labs are adequate for improving understanding of biology topics that are difficult to observe directly in the classroom context (Collier et al, 2012;Pope et al, 2017;Radhamani et al, 2014). For example, evolution by natural selection has been shown to be notoriously difficult for students to understand, and its processes have been described as not directly observable (Krist & Showsh, 2007;Nehm & Schonfeld, 2008;Plunkett & Yampolsky, 2010).…”
Section: Knowledge and Conceptual Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, various studies have shown that virtual labs are adequate for improving understanding of biology topics that are difficult to observe directly in the classroom context (Collier et al, 2012;Pope et al, 2017;Radhamani et al, 2014). For example, evolution by natural selection has been shown to be notoriously difficult for students to understand, and its processes have been described as not directly observable (Krist & Showsh, 2007;Nehm & Schonfeld, 2008;Plunkett & Yampolsky, 2010).…”
Section: Knowledge and Conceptual Understandingmentioning
confidence: 99%
“…While physical laboratories are absent or not fully equipped in many schools due to the high costs of their equipment and maintenance, virtual labs have been affirmed to lessen financial constraints related to laboratory equipment, space, and maintenance (Fisher et al, 2012). These potential advantages have triggered research interest, and a good number of empirical studies have been conducted about the effectiveness of virtual laboratories (Breakey et al, 2008;Dyrberg et al, 2017;Muhamad et al, 2010Muhamad et al, , 2012Pope et al, 2017;Radhamani et al, 2014;Ray et al, 2012;Triola & Holloway, 2011).…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…We identified 31 publications that referenced using the Concept Inventory for Natural Selection (CINS), one used some version of the instrument (Pope et al 2017), most likely administering a portion of the full instrument, 19 administered the instrument to a new population, and ten studies reported using the instrument with a new population and changing the question structure. A few of these studies reported additional evidence of reliability and validity.…”
Section: Secondary Uses Of Focal Instrumentsmentioning
confidence: 99%
“…Weisberg et al (2018) administered the CINS to a sample from the general public and reported Cronbach's alpha. Finally, Pope et al (2017) also report Cronbach's alpha and interrater reliability for biology majors in the northeast.…”
Section: Secondary Uses Of Focal Instrumentsmentioning
confidence: 99%
“…Student misconceptions regarding evolution are very resistant to instruction (Gregory, 2009), but can be improved with the series of activities and teaching strategies (e.g. Dees, Momsen, Niemi, & Montplaisir, 2014;Kalinowski, Leonard, Andrews, & Litt, 2013;Kampourakis & Zogza, 2008;Nehm and Schonfeld, 2007;Pope, Rounds, & Clarke-Midura, 2017). Nehm and Schonfeld (2007) found that students tend to retain only what is necessary to pass the exam before returning back to their original beliefs about evolution.…”
Section: Knowledge Of Evolutionmentioning
confidence: 99%